ANALISIS BUTIR SOAL USBN MATA PELAJARAN BAHASA INDONESIA DI SMA KABUPATEN ACEH BARAT - Lasmy Lasmy; Yusrizal Yusrizal; Razali Razali (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to find out the validity, reliability, difficulty level, differentiation, and function item problem of USBN casting in Bahasa Indonesia subjects at SMA Aceh Barat. The approach in this study is a quantitative approach. This research uses a type of quantitative descriptive research. The sample of this study amounted to 5 schools and this research data is 40 question from the answer sheet of 50 students in each school. Data collection techniques with document studies. The data analysis techniques in this study used the AnatesV4.02 program. Analysis of problem items with a computer is a quantitative review of the question item whose calculations use the anates V4.02 application. The results of this study showed that the validity of USBN problems in Bahasa Indonesia subjects at SMA Aceh Barat district obtained 74valid questions with a validity level of 0.32-0.40 and 126 invalid questions with a degree of invalidity of 0.20. This invalidity is caused by the inaccuracy of explanation of each material by the teacher in the school so that students are unable to understand about the essence of the sentence. Reliability of USBN subjects in Bahasa Indonesia at SMA West Aceh district shows 0.61-0.73 in high reliability category. High school that gained the low reliability category was SMA Woyla of value 0.31. This is because the low understanding of students so as to cause problems classified in is very difficult. The difficulty level of USBN problems in Bahasa Indonesia subjects in SMA Kabupaten Aceh Barat can be seen from the difficulty index between 0.00 to 1.0. The degree of difficulty that dominates the difficulty level in each question studied is in the moderate category. The difficulty of this medium problem is influenced by the inaccuracy of the material provided by the teacher so that the student is not able to understand it completely. In addition, the question that is used as an evaluation is born from materials that are not taught by the teacher. The differentiation of USBN subjects in Bahasa Indonesia at SMA Aceh Barat district shows the percentage value includes a very good differentiation question 2 questions, good 56 questions, enough 71, and bad 71 questions. A series of differentiating power quality levels of this question appears that the differentiation of problems with very good quality is less compared to the quality of the differentiation of the problem with the category of good, sufficient, and bad. This quality difference because each question does not go through a validation and reliable process so as to have an effect on the differentiating power of each question. The casting function of USBN subjects in Bahasa Indonesia at SMA Aceh Barat consists of five levels including very good